N-terminal pro-B-type natriuretic peptide in amniotic fluid of fetuses with known or suspected cardiac load. - Christina Leufgen; Ulrich Gembruch; Birgit Stoffel-Wagner; Rolf Fimmers; Waltraut M Merz (PLoS ONE, 2017)
BACKGROUND:Myocardial dysfunction occurs in a variety of fetal disorders. Findings from adult cardiology, where n-terminal pro-B-type natriuretic peptide (nt-proBNP) is an established biomarker of left ventricular dysfunction have been extended to fetal life. Since fetal blood sampling is technically challenging we investigated amniotic fluid nt-proBNP for its suitability to diagnose fetal myocardial dysfunction. METHODS:Ultrasound, Doppler examination and echocardiography was applied to classify cases and controls. Amniotic fluid nt-proBNP to amniotic fluid total protein ratio was calculated and compared to the gestational age-dependent reference intervals. In a subset of cases, fetal and maternal plasma nt-proBNP levels were determined. RESULTS:Specimen from 391 fetuses could be analyzed (171 cases, 220 controls). There was a high correlation between amniotic fluid and fetal blood nt-proBNP levels (r = 0.441 for cases; r = 0.515 for controls), whereas no correlation could be detected between maternal and fetal (blood and amniotic fluid) nt-proBNP concentrations. Specificity and positive likelihood ratio of amniotic fluid nt-proBNP to amniotic fluid total protein ratio were high (0.97 and 4.3, respectively). CONCLUSION:Amniotic fluid nt-proBNP measurement allows diagnostic confirmation of fetal myocardial dysfunction. It may serve as a useful adjunct in addition and correlation to existing tests of myocardial function, particularly in the context of invasive fetal therapy, where access to the amniotic cavity is part of the procedure.